The AU-rich sequences in the 3' untranslated region mediate the increased turnover of interferon mRNA induced by glucocorticoids (The Rockefeller University Press, 1991)
Different vectors were constructed that expressed the human interferon- beta (IFN-beta) mRNA constitutively and contained various deletions in the 3' untranslated region (UTR). AU-rich sequences in the 3' UTR were specifically deleted in two vectors. Cell lines secreting human IFN- beta were established by transfecting murine L929 cells with the vectors. These cells showed similar levels of IFN-beta mRNA and secreted comparable amounts of IFN-beta, indicating that the deletion of AU-rich sequences had no effect on the stability and little effect on the efficiency of translation of this mRNA. The synthetic glucocorticoid dexamethasone was previously shown to increase the turnover of IFN-beta mRNA. This activity of dexamethasone was clearly observed only in cells expressing IFN-beta mRNA with AU-rich sequences in the 3' UTR. The increased turnover of this mRNA occurred in the presence of cycloheximide; therefore, it did not require synthesis of new proteins. These findings suggest that glucocorticoids may activate a ribonuclease that degrades mRNAs containing AU-rich sequences in the 3' UTR.